Acute and Long-Term Toxicity of Mango Leaves Extract in Mice and Rats. (27th August 2014) - Zhang, Yi; Li, Jian; Wu, Zhizhen; Liu, Erwei; Shi, Pingping; Han, Lifeng; Guo, Lingling; Gao, Xiumei; Wang, Tao
Abstract : The acute toxicity of mango leaves extract (MLE) at the maximal dose (18.4 g/kg) was studied in ICR mice and no abnormalities were detected during the experiment. The long-term studies at various doses of MLE (100 mg/kg, 300 mg/kg, and 900 mg/kg) in SD rats for 3 consecutive months revealed that, compared with the control group, rats in MLE treated groups showed slight body weight increase and higher fat weight; the serum TG and CHOL levels and the epididymis weight of male rats were a little higher; the serum K + level of female rats was on the low side but the weights of liver, kidney, and adrenal gland were on the high side. In addition to this, no other obvious abnormalities were detected.